2015
DOI: 10.1016/j.bbamcr.2015.05.019
|View full text |Cite
|
Sign up to set email alerts
|

PAK1 is involved in sensing the orientation of collagen stiffness gradients in mouse fibroblasts

Abstract: Migrating cells sense variations of stiffness in connective tissue matrices but how cells detect and respond to stiffness orientation is not defined. We examined cell extension formation on collagen with underlying support (vertical stiffness gradient) or on collagen laterally supported by nylon (lateral stiffness gradient). At 6 h after plating, cells plated on laterally-supported collagen exhibited >2-fold more abundant and ~2-fold longer cell extensions than cells plated on collagen with underlying support.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 81 publications
(118 reference statements)
2
5
0
Order By: Relevance
“…39 Our use of the floating collagen gel model to model cell extension formation, matrix remodeling, and collagen degradation provided a rapid and integrated system to screen a large number of compounds as potential inhibitors of cancer cell invasion. Notably, the alignment of collagen fibers is temporally and spatially correlated with the generation of cell extensions, 40 and our results here generally showed that those compounds that inhibited cell extension formation also affected collagen alignment. In summary, screening compounds with the use of the grid-supported floating collagen gel model may facilitate the linkage of cancer cell biology with the identification of new inhibitor of cancer cell invasion.…”
Section: Discussionsupporting
confidence: 77%
“…39 Our use of the floating collagen gel model to model cell extension formation, matrix remodeling, and collagen degradation provided a rapid and integrated system to screen a large number of compounds as potential inhibitors of cancer cell invasion. Notably, the alignment of collagen fibers is temporally and spatially correlated with the generation of cell extensions, 40 and our results here generally showed that those compounds that inhibited cell extension formation also affected collagen alignment. In summary, screening compounds with the use of the grid-supported floating collagen gel model may facilitate the linkage of cancer cell biology with the identification of new inhibitor of cancer cell invasion.…”
Section: Discussionsupporting
confidence: 77%
“…Taken together, these processes contribute to increased cell extension formation. Our data presented here indicate that vimentin in focal adhesions plays a central role as an adaptor protein, which may contribute to mesenchymal cell migration and extracellular matrix remodeling (Pinto et al, 2015;Terriac et al, 2017). These processes, which are associated with EMT, are important for tissue regeneration and repair in wound healing (Stone et al, 2016).…”
Section: Discussionmentioning
confidence: 75%
“…After 24 h, local ECM remodeling was quantified by measuring collagen fiber alignment (35) visualized by confocal reflectance microscopy, as we have previously described (29,24,25,31). In brief, a fast Fourier transform was employed to quantify the distribution of collagen fiber angles referenced to the frame of the acquired image measured as pixel intensity at any given angle.…”
Section: H718 Monocyte-mediated Myofibroblast Activity and Ecm Remodelingmentioning
confidence: 99%